Three‐dimensional nanoporous activated carbon electrode derived from acacia wood for high‐performance supercapacitor - Hamouda, Hamouda Adam; Abdu, Hassan Idris; Hu, Qinzheng; Abubaker, Mohamed Aamer; Lei, Haikuo; Cui, Shuzhen; Alduma, Anwar I.; Peng, Hui; Ma, Guofu; Lei, Ziqiang (Frontiers in Chemistry, 2022)
Herein, the novel acacia wood based hierarchical porous activated carbons (AWCs) are easily prepared, low cost and have excellent characterization, such as special biomass nanopores via structural stability and large specific surface areas. Activating agents such as KOH, ZnCl2, and H3PO4 have been used to convert acacia wood carbon into active carbons such as AWC-K, AWC-Z, and AWC-P, respectively, which are named after the activating agent. As a supercapacitor electrode, the AWC-K sample has a high yield was 69.8%, significant specific surface area of 1563.43 m2g-1 and layer thickness of 4.6 mm. Besides that, it showed specific capacitance of 224.92 F g-1 at 0.5 A g-1 in 2 M KOH as electrolyte. In addition, the AWC-K//AWC-K symmetrical supercapacitor device displays high energy density of 23.98 Wh kg-1 at 450 W kg-1 power density with excellent cycling number stability was 93.2% long lifetime of 10000 cycles using 0.5 M Na2SO4 as electrolyte. The high electrochemistry performance mainly contributed the special biomass pores structure. Therefore, the presented approach opens new avenues in supercapacitor applications to meet energy storage.